2018
DOI: 10.1002/slct.201800174
|View full text |Cite
|
Sign up to set email alerts
|

2,4‐Disubstituted Phenylhydrazonopyrazolone and Isoxazolone Derivatives as Antibacterial Agents: Synthesis, Preliminary Biological Evaluation and Docking Studies

Abstract: A series of new 2,4-disubstituted phenylhydrazonopyrazolone and isoxazolones have been synthesized and evaluated for antibacterial activity. These compounds incorporated the bioactive moieties 3-methyl isoxazolone and 3-methyl pyrazolone. Based on the preliminary results, evaluation of these new compounds as potential antimicrobial agents revelead that four of them which incorporate the isoxazolone moiety exhibited selective antimicrobial activity against Gram-positive bacteria with MICs for S. aureus in the 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…Oraby and teammates [34] synthesized 2,4-disubstituted phenylhydrazonopyrazolone and isoxazolone analogues as antibacterial agents. The results of antibacterial test suggested that the compounds contain the scaffold of pyrazolone like 51 and 52 ( Fig.…”
Section: Pyrazolones As Antimicrobial Agents and Their Sarmentioning
confidence: 99%
“…Oraby and teammates [34] synthesized 2,4-disubstituted phenylhydrazonopyrazolone and isoxazolone analogues as antibacterial agents. The results of antibacterial test suggested that the compounds contain the scaffold of pyrazolone like 51 and 52 ( Fig.…”
Section: Pyrazolones As Antimicrobial Agents and Their Sarmentioning
confidence: 99%
“…We recently applied an MCR to the synthesis of isoxazol-5(4 H )-one (ISX) derivatives, an important class of heterocyclics with potential and diverse biological activities [ 161 , 162 , 163 , 164 , 165 , 166 ], by using a synthetic enzyme (synzyme) that we had previously reported [ 167 ] as an efficient catalyst to perform ISX syntheses ( Scheme 11 ) [ 168 ]. Some of these MCR adducts had fluorescent properties and could be applied in cell-imaging experiments as selective bioprobes.…”
Section: The Combined Role Of Catalysis and Solvent Effects In Mcrsmentioning
confidence: 99%
“…In consideration of the aforementioned background and with the extension of our former investigations on benzoxazole moiety and its innate pharmacological activities [14,[29][30][31][32][33], we describe the preparation of a new series of compounds with 3-benzoxazolyl aniline scaffold ( Figure 2). All the analogs were screened for their antimicrobial, antimalarial, antileishmanial, and antitrypanosomal activities.…”
Section: Introductionmentioning
confidence: 99%